RESPON INDONESIA TERHADAP ACFTA: PRO KONTRA WACANA RENEGOSIASI - Elisabeth Kartikasari (Cakrawala Jurnal Penelitian Sosial, 2014)
This study aimed to analyze the response of Indonesia concerning the implementation of the ACFTA to be addressed differently. This response refers to the ACFTA agreement renegotiation discourse which then led to a debate among actors from government, industry associations representative body of the people and environment of researchers both for and were refused. The main question of this study is to determine aspects of the contentious arguments of the actors are pros and cons discourse ACFTA renegotiation. By knowing the contentious aspects of the follow-up question arises which will lead to the background of the debate the pros and cons of discourse in Indonesia ACFTA renegotiation between the actors concerned.The principles of neoliberalism and Keynesianism approach will be used as a tool to analyze the debate discourse renegotiation Asean China Free Trade Agreement within the domestic sphere. This study uses a qualitative method using data obtained from textbooks, journals, newspaper articles and online. Secondary data from interviews of relevant actors processed from articles in the media.The research findings indicate that the differences in the arguments of each group of actors that are grouped into three aspects: economic, political and social fields. Actor pro renegotiation based on principles of Keynesianism which assumes that under conditions likely to lose money, the state must do more to protect the domestic industry was the actor who cons ACFTA renegotiation argue in an effort to accelerate economic growth and strengthening of the ASEAN region. Differences of opinion in view of ACFTA is located on the state's role in addressing the ACFTA, differences in economic interests and differences in the political orientation of the actors involved in the ACFTA agreement. Keywords: Asean China Free Trade Agreement, Discourse Renegotiation, Neoliberalism, Keynesianism